Evaluation of Prehospital Blood Products to Attenuate Acute Coagulopathy of Trauma in a Model of Severe Injury and Shock in Anesthetized Pigs. (August 2015) - Watts, Sarah; Nordmann, Giles; Brohi, Karim; Midwinter, Mark; Woolley, Tom; Gwyther, Robert; Wilson, Callie; Poon, Henrietta; Kirkman, Emrys
Abstract : ABSTRACT: Acute trauma coagulopathy (ATC) is seen in 30% to 40% of severely injured casualties. Early use of blood products attenuates ATC, but the timing for optimal effect is unknown. Emergent clinical practice has started prehospital deployment of blood products (combined packed red blood cells and fresh frozen plasma [PRBCs:FFP], and alternatively PRBCs alone), but this is associated with significant logistical burden and some clinical risk. It is therefore imperative to establish whether prehospital use of blood products is likely to confer benefit. This study compared the potential impact of prehospital resuscitation with (PRBCs:FFP 1:1 ratio) versus PRBCs alone versus 0.9% saline (standard of care) in a model of severe injury. Twenty-four terminally anesthetised Large White pigs received controlled soft tissue injury and controlled hemorrhage (35% blood volume) followed by a 30-min shock phase. The animals were allocated randomly to one of three treatment groups during a 60-min prehospital evacuation phase: hypotensive resuscitation (target systolic arterial pressure 80 mmHg) using either 0.9% saline (group 1, n = 9), PRBCs:FFP (group 2, n = 9), or PRBCs alone (group 3, n = 6). Following this phase, an in-hospital phase involving resuscitation to a normotensive target (110 mmHg systolic arterial blood pressure) using PRBCs:FFP was performed in all groups. There was no mortality in any group. A coagulopathy developed in group 1 (significant increase in clot initiation and dynamics shown by TEG [thromboelastography] R and K times) that persisted for 60 to 90 min into the in-hospital phase. The coagulopathy was significantly attenuated in groups 2 and 3 ( P = 0.025 R time and P = 0.035 K time), which were not significantly different from each other. Finally, the volumes of resuscitation fluid required was significantly greater in group 1 compared with groups 2 and 3 ( P = 0.0067) (2.8 ± 0.3 vs. 1.9 ± 0.2 and 1.8 ± 0.3 L, respectively). This difference was principally due to a greater volume of saline used in group 1 ( P = 0.001). Prehospital PRBCs:FFP or PRBCs alone may therefore attenuate ATC. Furthermore, the amount of crystalloid may be reduced with potential benefit of reducing the extravasation effect and later tissue edema.